A SOA-based Middleware to Integrate Chatterbots in e-Learning Systems - Caeiro, Manuel; Fontenla, Jorge; Mikic, Fernando; Perez, Roberto; Llamas, Martin; Burguillo, Juan C. (Cadernos de Informática, 2011)
In recent years, artificial intelligence conversational agents, usually known as chatterbots, have become very popular in the Internet. In this paper we show how chatterbots can be integrated in e-learning systems. To perform such integration the Service Oriented Architecture programming paradigm is adopted. A middleware is provided for enabling the integration and reuse of chatterbots by e-learning systems supporting a tight control of their operation. Such middleware takes into account several issues such as user authorization, instance creation, data transfer to and from the chatterbot, permission assignment to users and subscription to events. Our approach is applied to the specific case of TQ-Bot, which is used to track and supervise the progress of the students, and to provide answers orienting them to the more appropriate course contents.